PENGEMBANGAN SUMBER DAYA LOKAL DI KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT (STUDI KASUS: PENGELOLAAN GAMBIR DI KECAMATAN PANGKALAN KOTO BARU) - Rozi Saputra; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The Management of gambir as a featured commodity of Lima Puluh Kota Regency and Pangkalan Koto Baru Sub-district is very important. It’s because of gambir commodity is a featured commodity and contributes greatly to the Regional Domestic Product of Lima Puluh Kota particularly and West Sumatra in general. Based on field observation, there are some problems regarding lack of utilization of gambir land compared, lack of proper use of technology in gambir processing, low quality of gambir products and makes gambier derivative products don’t have much variation also impact to price fluctuations. The purpose of this research are to know how the management of Gambir at Pangkalan Koto Baru is and any factors may affect the processing of gambir in this sub-district.The concept of theory used is the management theory by George R.Terry which starts with planning, organizing, actuating and controlling. This research uses qualitative descriptive research method. The type of data used is primary data and secondary data. In the data collecting, researchers use observation techniques, interviews, literature study and documentation. Interviews were conducted with key informants.The result of this research is that the management of Gambir in Pangkalan Koto Baru Sub-district of Lima Puluh Kota has not been maximized. There are still major shortcomings in planning, organizing and controlling. Then the factors that become obstacles in Gambir management at Pangkalan Koto Baru Sub-district are institutional, budget, facilities and infrastructure and market.Keywords: Management, Local Resources Development, Gambir